Impact of COVID-19 attributable deaths on Longevity, Premature Mortality and DALY: Estimates of USA, Italy, Germany and Sweden (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: COVID-19; mortality; life expectancy; USA; italy; germany; sweden